Development of a grau model for simulating cephalexin residue removal from wastewater by using lemna minor. Issue 1 (1st January 2021) - Alquzweeni, Saif S.; Al-Zubaidi, Hussien A. M.; Samaka, Isra'a S.; Albahadily, Aqeel R.
Abstract: Removal of cephalexin residues from wastewater is one of the most concerned issues in treatment plants due to the growing of the antibiotics consumption level around the world. In this study, the impact of the initial concentration of cephalexin residues on its removability by lemna minor was investigated by developing a grau model accounting for the cephalexin initial pH value. In the model, the second-order kinetic constants of adsorption were linked linearly with the influent pH values. Results showed that using lemna minor along with phytoremediation process increased the removal efficiency value to 86.5% and dropped chemical oxygen demand (COD) to 0.012 mg/L in effluent, making the removability of cephalexin from the polluted water easier. In addition, it was found that changing the grau model kinetic constants linearly (positively or negatively) with pH affects the removal efficiency. Based on the results, the best removability can be noticed at the pH level of 7 with a value of 71%.